Islamic Banking and its Impact on the Investment and Employment in the Private Sector: An econometric study on the countries of the Gulf Cooperation Council (GCC) during the period 2005-2017 - Asaad, Mohammed Al-Emad; Ben Mimoun, Mohamed (Journal of Economic, Administrative and Legal Sciences, 2021)
This paper aimed to analyze the impact of both conventional and Islamic banks’ financing on capital investment and labor employment in the non-oil private sector of the Gulf Cooperation Council countries. It also shed light on the impact of the structure of Islamic finance (participatory financing versus debt financing) on these two variables. The study relied on estimating standard models that show the determinants of the demand for capital investment and labor, including conventional and Islamic banks’ financing. The study used Panel-data and appropriate estimation methods over the 2005-2017 period. The most important econometric results showed that capital investment and labor employment are positively and significantly affected by both types of financing, with conventional financing effects exceed the ones of Islamic counterpart. The results also showed that Islamic finance in participatory formats had the greatest marginal effects compared to debt-financing formats on investment in the private sector (and on employment, but not-conclusively) in the countries under the study. Among the recommendations of the study for these countries, one can suggest more Islamic banking support in order to further stimulate investment and reduce unemployment, with a particular focus on participatory-formats comparatively to debt-formats, as they have greater marginal effects on these two variables. * يتقدم الباحثان بالشكر الجزيل لعمادة البحث العلمي بجامعة أم القرى لدعم وتمويل هذا المشروع رقم ADM-5-06-0001 - 18 والذي ساهم بفعالية في إنجاز مراحل هذا المشروع. *(Acknowledgement: The authors would like to thank the Deanship of Scientific Research at Umm Al-Qura University for supporting this work by Grant Code: 18 - ADM-5-06-0001.